2023
DOI: 10.1021/acsnano.3c07571
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared-II In Vivo Visualization and Quantitative Tracking of Micro/Nanoplastics in Fish

Lanpeng Yang,
Ben Zhong Tang,
Wen-Xiong Wang

Abstract: As emerging contaminants, micro/nanoplastics (MNPs) are widely present in aquatic environments and are often ingested by aquatic organisms. However, the in vivo trafficking and fate of MNPs remain largely unknown. Here, we developed near-infrared (NIR) aggregated-induced emission (AIE) fluorophore-labeled microplastics (2 μm) and nanoplastics (100 nm) as models of MNPs. This model was based on the NIR-AIE technique with strong emission at the second near-infrared (NIR-IIII) window, which overcomes the interfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 70 publications
(138 reference statements)
0
1
0
Order By: Relevance
“…MNPLs have become ubiquitous in the environment, even in places where human activities are less. 3 Identifying the possible sources of MNPLs is also important to reduce their environmental risks. In the manufacturing process of commercial MNPLs, some additives such as inorganic and organometallic compounds are usually added to broaden their application as heat stabilizers, fillers, pigments, fungicides, and flame retardants.…”
Section: Traceability Of Mnpls In Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…MNPLs have become ubiquitous in the environment, even in places where human activities are less. 3 Identifying the possible sources of MNPLs is also important to reduce their environmental risks. In the manufacturing process of commercial MNPLs, some additives such as inorganic and organometallic compounds are usually added to broaden their application as heat stabilizers, fillers, pigments, fungicides, and flame retardants.…”
Section: Traceability Of Mnpls In Environmentmentioning
confidence: 99%
“…Secondary MPLs are formed from larger plastics in the environment due to UV-induced degradation, hydrolysis and biodegradation processes, or during use. 3 Due to the potential ecological and health impacts of MPLs in the environment, researchers have suggested to consider mechanical breaking down plastic fragments to a lower scale (sub-micron scale). Nanoplastics (NPLs) are defined as unintentionally produced particles during the manufacture and degradation of plastic objects and exhibit colloidal behavior, with sizes ranging from 1 to 1000 nm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Digestive organs (e.g., gut and intestines) are widely recognized as the primary target for the accumulation of MPs in fish. , In recent years, a previously overlooked but MP-sensitive organ (i.e., gills) in fish has attracted increasing attention. It was demonstrated that the proportion of the retained polystyrene (PS) in gills of medaka Oryzias melastigma can reach more than 10% .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the degradable MPs (i.e., PLA MPs) likely displayed higher fragmentation rates, removal efficiency, and egestion rates compared to persistent PE and PVC MPs. We further synthesized two functionalized biocompatible fluorescent probes (esterase activity and acidification) using the AIE technique based on previous literature, 33,36 and unraveled how the intestinal responses may affect the in vivo biodegradation of MPs in the plastic-degrading insect. We discovered that the plastivore insect, T. molitor larvae, could instinctively modulate their internal digestive environment in response to the biodegradation of various MPs.…”
Section: ■ Introductionmentioning
confidence: 99%